Fermented Pulut Corn Milk Processing Training As Community Empowerment Efforts Bumi Bahari Village, Gorontalo Province - Syam S. Kumaji; Astin Lukum; Margaretha Solang; Muhammad Isra; Asniwati Zainuddin; Widya Rachmawaty Saman (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Pulut corn has various physicochemical characteristics compared to non-pulut corn. Adequate nutritional content makes pulut corn potentially capable of supporting the diversification of the food industry, one of which is used as fermented corn milk. The purpose of implementing this activity is for the community to gain knowledge about the processing of corn pulut as fermented milk. The activity was carried out in Bumi Bahari Village, Popayato District, Pohuwato Regency, Gorontalo Province in November 2022. The resulting data were analyzed descriptively which described the implementation of the activities, including preparation and implementation. Based on the results of observations, it was found that the people involved were very enthusiastic and showed a positive and independent attitude during the activity process. In addition, from the results of interviews with the training participants, it was found that they were greatly helped by this training activity. So far, the training participants only know that pulut corn is processed as boiled pulut corn, and Gorontalo's special food.